Entre o sofrimento e a esperança: A reabilitação da incontinência urinária como componente interveniente - Delarmelindo, Rita de Cássia Altino; Parada, Cristina Maria Garcia de Lima [UNESP]; Rodrigues, Rosalina Aparecida Partezani; Bocchi, Silvia Cristina Mangini [UNESP] (FapUNIFESP (SciELO), 2013)
This is a qualitative study seeking to understand Brazilian women's experience of urinary incontinence (UI) and design a representative theoretical model for the experience. Theoretical saturation occurred after analysis of the 18th non-directive interview in accordance with Grounded Theory. Two phenomena emerged: living with the challenges of UI and experiencing the hope and disappointment of rehabilitation from UI. Upon re-alignment of the components, the core category emerged, namely: between suffering and hope - rehabilitation from urinary incontinence as an intervening component. From the analysis in light of symbolic interactionism, pregnancy and vaginal birth were observed to be symbols of women's vulnerability to the suffering from living with the moral and physio-psychosocial challenges of UI. It is also inferred that the lack of consideration of the Unified Health System (SUS) in investing in the process of rehabilitation from UI may be having a negative effect on the incentive programs for promoting vaginal birth. Most of all, it reveals the ongoing suffering of women with UI, most of whom do not have access to rehabilitation due to the lack of programs geared to the real needs of these users of the Unified Health System.
Between suffering and hope: Rehabilitation from urinary incontinence as an intervening component
Keywords: Life-changing events; Psychosocial effects of the disease; Qualitative research; Urinary incontinence; Women's health